The effectiveness of prenatal gentle yoga and effleurage massage on reducing back pain in pregnant women in the third trimester at PMB riska indraweni, Lumajang Regency - Wiwin Septyaningsih; Erma Retnaningtyas; Retno Palupi Yoni Siwi (Institute Of Computer Science (IOCS), 2025)
Back pain in pregnant women can cause stress, thus increasing the risk of premature labor. Efforts to reduce pain are with prenatal gentle yoga and Effleurage Massage. This study aims to compare the effectiveness of prenatal gentle yoga and effleurage massage in reducing back pain in pregnant women at PMB Riska Indraweni, Lumajang Regency. The pre-experimental research design was Two Group Pretest-Posttest. The research method used was paired sample t-Test. The difference test of two paired samples was determined by purposive sampling and each group of prenatal gentle yoga and effleurage massage obtained 16 pregnant women who experienced back pain. The results of the study showed that the average test in each treatment group showed significant results (p = 0.0001) with a difference in the average decrease in back pain intensity in the prenatal gentle yoga group of 0.31 and the effleurage massage group of 0.6. The effleurage massage technique has a higher effectiveness than prenatal yoga in reducing back pain in pregnant women. Pregnant women are advised to apply effleurage massage and prenatal gentle yoga to overcome back pain and more in-depth research is needed regarding the causes of back pain in pregnant women.